2018
DOI: 10.1302/2046-3758.71.bjr-2017-0143.r1
|View full text |Cite
|
Sign up to set email alerts
|

A computational simulation study to determine the biomechanical influence of posterior condylar offset and tibial slope in cruciate retaining total knee arthroplasty

Abstract: ObjectivesPosterior condylar offset (PCO) and posterior tibial slope (PTS) are critical factors in total knee arthroplasty (TKA). A computational simulation was performed to evaluate the biomechanical effect of PCO and PTS on cruciate retaining TKA.MethodsWe generated a subject-specific computational model followed by the development of ± 1 mm, ± 2 mm and ± 3 mm PCO models in the posterior direction, and -3°, 0°, 3° and 6° PTS models with each of the PCO models. Using a validated finite element (FE) model, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 58 publications
(87 reference statements)
0
24
0
1
Order By: Relevance
“…Higher quadriceps muscle and patellar tendon force are required as the posterior condylar offset moved in the anterior direction with an equivalent flexion angle. The forces exerted on the PCL increased as posterior condylar offset moved in the posterior direction (Kang, Koh, Son, Kwon, Lee and Kwon, 2018c). They found that change in posterior condylar offset alternatively provided positive and negative biomechanical effects.…”
Section: Application Of Computational Simulation In Pre-or Post-clinimentioning
confidence: 99%
See 2 more Smart Citations
“…Higher quadriceps muscle and patellar tendon force are required as the posterior condylar offset moved in the anterior direction with an equivalent flexion angle. The forces exerted on the PCL increased as posterior condylar offset moved in the posterior direction (Kang, Koh, Son, Kwon, Lee and Kwon, 2018c). They found that change in posterior condylar offset alternatively provided positive and negative biomechanical effects.…”
Section: Application Of Computational Simulation In Pre-or Post-clinimentioning
confidence: 99%
“…7). Such studies have been performed in both FE and MBD models (Essner et al, 2011;Kang et al, 2018a;Kang et al, 2016;Kang et al, 2017f;Kang et al, 2018b;Kang et al, 2018c;Kang et al, 2018e;Kang et al, 2019b;Kang et al, 2018g;Kuriyama et al, 2014;Marra et al, 2018;Suh et al, 2017;Thompson et al, 2011). Investigations have included pre-or post-clinical evaluation for translation and rotation in coronal and sagittal planes.…”
Section: Application Of Computational Simulation In Pre-or Post-clinimentioning
confidence: 99%
See 1 more Smart Citation
“…2). Ein Verlust an posteriorem Kondylenoffset bedingt ein reduziertes femorales Rollback und kompromittiert damit die Beugefähigkeit und Stabilität [16,17]. Da trotz der angesprochenen Radiendifferenzen die konkreten Unterschiede der Femurgeometrien letztendlich im Millimeterbereich liegen, ist aufseiten des Femurs die akkurate Operationstechnik von entscheidenderer Bedeutung als das vorliegende Implantatdesign anzusehen.…”
Section: Introductionunclassified
“…Kang et al 1 have ably demonstrated the role of finite element analysis (FEA) in deciphering the complex interplay between component positioning of the implanted total knee arthroplasty (TKA) and the kinetics of key soft-tissue structures. This work extends our knowledge of the role of the central posterior restraint (posterior cruciate ligament (PCL)) and the impact of varying posterior condylar offset (PCO) and posterior tibial slope upon final tibiofemoral flexion, muscle load, and by inference, final construct stability.…”
mentioning
confidence: 99%